LIMIAR DE RECONHECIMENTO DO GOSTO SALGADO E ESTIMATIVA DE CONSUMO DE SÓDIO DE TRANSPLANTADOS RENAIS - Lúcia Chaise Borjes; Jéssica Maiara Rosetto; Liandra Martins Garcia (Universidade do Estado do Rio de Janeiro, 2015)
Objectives: The study aimed to evaluate the threshold of saltytaste recognition and the estimate of sodium intake amongkidney-transplant recipients who attend the renal clinic inChapecó, Santa Catarina, Brazil. Methods: Study with descriptivenature, quantitative approach, based on a case study. Thesample consisted of 52 patients, who tasted saline solutions untilrecognizing the lowest concentration of salty taste. The thresholdwas represented by the average value of concentrations where"recognition" and "non-recognition" occurred. Other data werecollected from medical records. Results: Most of the sample(63.5%) showed a threshold regarded as normal or below normal,i.e. less than or equal to 0.01 mol/l (0.91 g/l) and the average saltintake was 10.7 g/day, estimated from urinary sodium excretion.There was no significant association between the classificationof salty taste recognition thresholds and some of the variablesunder study, namely: age, gender, body mass index (BMI), bloodpressure, antihypertensive drug use, and estimated salt intakefrom urinary sodium. However, if evaluating the associationbetween the amount of the lowest concentration recognizing saltytaste and age, it shows up as statistically significant (rs = 0.339;p = 0.014). Older patients had higher salty taste recognitionthresholds. Conclusion: Although there is a need for furtherresearch on the subject, a high estimate of salt intake fromurinary sodium is observed, and this reality should be carefullyaddressed, especially for elderly patients, who have a higher saltytaste recognition threshold and may increase salt intake to makefood more pleasant to their taste. Not only kidney-transplantrecipients, but also the Brazilian population as a whole, requirepublic health actions to reduce salt intake. DOI: 10.12957/demetra.2015.14092